Intensive care unit versus high-dependency care unit for mechanically ventilated patients with pneumonia: a nationwide comparative effectiveness study - Hiroyuki Ohbe, MD; Yusuke Sasabuchi, PhD; Hayato Yamana, PhD; Hiroki Matsui, MPH; Hideo Yasunaga, PhD (Elsevier, 2021)
Background: : Many mechanically ventilated patients in Japan are treated in high-dependency care units (HDUs) rather than intensive care units (ICUs). HDUs can provide intermediate-level care with reduced costs; however, there is limited evidence on whether mechanically ventilated patients should be treated in the ICU or HDU. Methods: : This was a comparative effectiveness study using a nationwide administrative database in Japan. We identified mechanically ventilated patients with pneumonia in ICU or HDU on the day of admission in the Japanese Diagnosis Procedure Combination inpatient database from April 2014 to March 2019. The primary outcome was 30-day in-hospital mortality. Propensity score matching analysis was performed to compare this outcome between patients treated in the ICU and HDU. The robustness of the analyses was evaluated with multivariable regression, overlap weighting, and instrumental variable analyses. Findings: : Of 14,859 mechanically ventilated patients with pneumonia, 7,528 (51%) were treated in the ICU and 7,331 (49%) were treated in the HDU. After propensity score matching, patients treated in the ICU had significantly lower 30-day in-hospital mortality than did those treated in the HDU (24.0% vs. 31.2%; difference, −7.2%; 95% confidence interval, −10.0% to −4.4%). The multivariable regression, overlap weighting, and instrumental variable analyses showed a similar direction and magnitude of association. Interpretation: : Critical care for mechanically ventilated patients with pneumonia in the ICU was associated with a 7.2% decrease in 30-day in-hospital mortality vs. care in the HDU. Residual confounding may still play a role in the effect estimates. Funding: : This study received funding from Ministry of Health, Labour and Welfare, Japan, and Ministry of Education, Culture, Sports, Science and Technology, Japan.